IMPLEMENTATION OF DIGITAL MARKETING MANAGEMENT AND TECHNOLOGY LITERACY TO BUILD PERSONAL BRANDING OF SATYAGAMA UNIVERSITY STUDENTS - Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2022)
The development of digital technology encourages students to utilize social media as a means of building a professional personal brand. This study aims to analyze the implementation of digital marketing management and technological literacy in shaping the self-image of Satyagama University students in the digital era. The research method used a quantitative approach through the distribution of questionnaires to active students at Satyagama University who use social media for communication and self-promotion. The results show that technological literacy skills and an understanding of digital marketing have a positive influence on students' ability to build a creative, professional, and competitive personal brand.